Notes about Legitimate Defense in Brazilian Criminal Law - Holanda Dias, Gustavo Henrique (Revista Jurídica Portucalense, 2015)
Self-defense is a human’s natural reaction, reflecting its self-preservation instinct. Crime is the typical behavior, illegal and culpable. In this concept, the illegality or unlawfulness of action is related to the setback of human’s action in face of legal system In Brazil the chance of unlawfulness or antijuridicidade exclusion are in criminal’s law. Self-defense represents an undisputed, inalienable and irreversible individual’s right which aims to personal and protection in face of another’s unjustified attack, repelling force by force, aggression by facing aggression. Among the exclusionary’s causes of unlawful, there is the self-defense.